Differential expression pattern, bioinformatics analysis, and validation of circRNA and mRNA in patients with arteriosclerosis - Liu, Yunyun; Wang, Kangjie; Li, Guanhua; Chen, Zhibo (Frontiers in Cardiovascular Medicine, 2022)
Lower limb arteriosclerotic occlusion(ASO) is the formation of atherosclerotic plaques in lower limb arteries, resulting in vascular stenosis and occlusion, which is the main factor leading to lower limb amputation. ASO seriously endangers the physical and mental health of patients.With the improvement of living standards, the incidence of the disease tends to be younger, and the incidence is increasing year by year. CircRNAs were found to be tissue specificity and played an important role in a variety of diseases, but there were few studies about the pathogenic role and expressions of circRNAs in ASO. In this study, the diseased arteries of ASO patients and healthy arteries from healthy donors were collected for second-generation sequencing, the pathogenic pathways and possible pathogenic circRNAs related to ASO were searched through bioinformatics analysis. PCR and agarose gel electrophoresis were used to verify the sequencing results. We found a total of 480 differentially expressed(DE) circRNAs and 2997 differentially expressed mRNAs. According to our previous microRNA array results, we constructed the ASO disease-specific ceRNA network. After verification, circRNA-0008706 was selected for functional analysis. siRNA technology was used to knock down the expression of circRNA-0008706 in human arterial smooth muscle cell(HASMC) to explore its function. The results showed that knockdown of circRNA-0008706 significantly inhibited the proliferation and migration phenotype of HASMC, which may be due to circRNA-0008706's specific binding of microRNA-125b-5p. In this study, circRNA and mRNA expression profiles in ASO and healthy arterial specimens were compared for the first time, and ASO disease-specific ceRNA network was constructed.This study may provide a new therapeutic target for ASO.